The perceived impact of legalized cannabis on nursing workload in adult and pediatric emergency department visits: A qualitative exploratory study. Issue 1 (26th August 2019) - Wolf, Lisa A.; Perhats, Cydne; Clark, Paul R.; Frankenberger, Warren D.; Moon, Michael D.
Abstract: Objective: To investigate changes in emergency nursing workload related to cannabis ingestion or inhalation by adult and pediatric patients in states and bordering states where recreational cannabis is legal. Design: Qualitative exploratory design using data collected from focus groups. Sample: Twenty‐four English‐speaking emergency nurses over the age of 18 who provide direct care to patients and work in US emergency departments located in a state, or bordering state, where recreational cannabis use is legal. Measurements: Qualitative data were gathered using a semi‐structured interview format and analyzed using situational analysis. Results: The legalization of recreational cannabis in some US states is reported as resulting in an increase in patients presenting with cyclic vomiting syndromes, and increased difficulty in managing both associated behaviors and repetitive ED presentations. New presentations also include unintentional intoxication in both pediatric and geriatric populations. An unexpected finding was the displacement of local homeless populations by younger, indigent "cannabis tourists"; social services agencies might consider this while planning for cannabis legalization in their state or territory. Conclusions: To protect public health and safety, regulatory efforts to standardize the formulation, dosing and labeling of cannabis products would be beneficial along with educational initiatives for both consumers and health care providers.